1990
DOI: 10.1164/ajrccm/141.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response Effects of Two Sizes of Monodisperse Isoproterenol in Mild Asthma

Abstract: The dose-response effect of monodispersed isoproterenol of two different sizes (diameters 2.5 and 5 microns) was examined in eight mild asthmatic subjects (baseline FEV, 81.5% of predicted). Pulmonary and cardiovascular variables were measured before and following 1, 2, 4, 8, and 16 cumulative min of aerosol inhalation. Subjects inhaled 1 to 30 micrograms (2.5-microns particles) or 2 to 50 micrograms (5-microns particles) of isoproterenol. Pulmonary but not cardiac responses were significantly greater for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 8 publications
0
12
1
1
Order By: Relevance
“…[8][9][10][11][12] However, in patients with chronic obstructive pulmonary disease, the ideal size ranges from 2 to 3 µm. [13][14][15][16] The size and density of aerosol particles are classified according to a mass median aerodynamic diameter (MMAD). For uniform-sized spherical particles, MMAD is defined as the particle diameter multiplied by the square root of the particle density.…”
Section: Advances In Inhalation Therapy In Pediatricsmentioning
confidence: 99%
“…[8][9][10][11][12] However, in patients with chronic obstructive pulmonary disease, the ideal size ranges from 2 to 3 µm. [13][14][15][16] The size and density of aerosol particles are classified according to a mass median aerodynamic diameter (MMAD). For uniform-sized spherical particles, MMAD is defined as the particle diameter multiplied by the square root of the particle density.…”
Section: Advances In Inhalation Therapy In Pediatricsmentioning
confidence: 99%
“…Particles above 5 pm in diameter are most likely to be deposited in the mouth and throat; thus, most of these are eventually swallowed. A study of eight patients with mild asthma who inhaled isoproterenol particles of 2.5 and 5 pm in diameter showed that the percentage increases (from baseline] in FEVl, SGaw and FEF25-75, and the decrease in FRC, were greater for the smallest particles ( 6 ) . These lung-function results also suggest a fairly even spread of drug throughout the airways for both formulations.…”
Section: Particle Size and Lung Depositionmentioning
confidence: 99%
“…In general, those aerosols with mass medium aerodynamic diameter (MMAD) < 5 pm produce optimal response, whether the aerosol is inhaled from a MDI (Rees et al, 1982) or jet nebulizer (Johnson et al, 1989;Patel et al, 1990). However, it is evident from the studies shown in Table 6 that inhalation of equal drug doses generated as different sized aerosols, can produce equivalent responses despite differences in particle size and initial distribution of the aerosol within the lung (Dolovich et al, 1981a;Mitchell et al, 1987;Wollmer et al, 1987).…”
Section: Aerosol Particle Sizementioning
confidence: 99%